2001
DOI: 10.1097/00004032-200105000-00011
|View full text |Cite
|
Sign up to set email alerts
|

COMPARISON OF ANGULAR FREE-IN-AIR AND TISSUE-EQUIVALENT PHANTOM RESPONSE MEASUREMENTS IN p-MOSFET DOSIMETERS

Abstract: Metal Oxide Semiconductor Field Effect Transistor (MOSFET) radiation dosimeters have found recent application in providing real-time measurement in diagnostic radiology as well as in radiotherapy. Due to the design of the MOSFET dosimeter, the response is dependent on both energy and angulation with respect to the direction of primary radiation. The axial angular dependence has been characterized for both free-in-air and for tissue-equivalent phantoms. However, neither the angular dependence normal (90-degree)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 6 publications
(37 reference statements)
1
21
0
Order By: Relevance
“…A standard deviation of 0.5 mV/Gy is obtained from −90 to 90 • of incidence, corresponding with an uncertainty of 5%. This uncertainty is similar to or even below that of other pMOS dosimeters [5][6][7]27,28]. Moreover, no memory effect is observed when irradiating in a different order with different incidence angles.…”
Section: Angular Dependencesupporting
confidence: 73%
“…A standard deviation of 0.5 mV/Gy is obtained from −90 to 90 • of incidence, corresponding with an uncertainty of 5%. This uncertainty is similar to or even below that of other pMOS dosimeters [5][6][7]27,28]. Moreover, no memory effect is observed when irradiating in a different order with different incidence angles.…”
Section: Angular Dependencesupporting
confidence: 73%
“…11 Our methodology ensures the delivery of constant exposure in the sensitivity evaluation. 2,9 All dosimeter models showed a linear response to exposure for the tube potentials and tube currenttime stations evaluated as shown in Figs. 11-14.…”
Section: Resultsmentioning
confidence: 89%
“…Both the simulation and the measurement indicate that the MOSFET dosimeter shows a higher response ͑by ϳ8%͒ for photons coming from the epoxy side, compared with photons from the kapton side. Pomijie et al 28 also observed a similar trend, but their angular dependence was much larger ͑ϳ20%͒. This difference is because they used much lower photon energies ͑90 kVp x rays͒.…”
Section: A Measurement Of Cs-137 From Different Directionsmentioning
confidence: 78%